Optimalisasi Metode Penyemaian Awan untuk Meningkatkan Curah Hujan - Nurinnadiyah Rahadatul 'Aisy; Hendratmoko, Ahmad Fauzi; Kamila, Nina Najwa; Sa'idah, Zhahirah Indana (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Jakarta, 2024)
Water scarcity is a serious environmental issue impacting many countries worldwide. Cloud seeding is a technology aimed at increasing rainfall by adding certain chemicals to clouds. Cloud seeding can enhance rainfall by up to 10%, which can support the water needs of additional households annually. The purpose of this literature review is to identify the most effective cloud seeding methods. The search was conducted using the SCOPUS database. The articles found were then selected based on their titles, keywords, and abstracts to ensure relevance to the research topic, resulting in 7 relevant articles. The literature review revealed various cloud seeding methods, such as Weather Research and Forecasting (WRF) cloud seeding, hygroscopic cloud seeding, and ECMWF cloud seeding. Based on an analysis of the advantages and disadvantages of these three cloud seeding methods, the most effective method is WRF cloud seeding because it is highly flexible and can be adapted to various weather conditions and topographies.